Thermospin effects in parallel coupled double quantum dots in the presence of the Rashba spin-orbit interaction and Zeeman splitting - Xue, Hui-Jie; Lü, Tian-Quan; Zhang, Hong-Chen; Yin, Hai-Tao; Cui, Lian; He, Ze-Long (Chinese physics B, 2012)
The thermoelectric and the thermospin transport properties, including electrical conductivity, Seebeck coefficient, thermal conductivity, and thermoelectric figure of merit, of a parallel coupled double-quantum-dot Aharonov-Bohm interferometer are investigated by means of the Green function technique. The periodic Anderson model is used to describe the quantum dot system, the Rashba spin-orbit interaction and the Zeeman splitting under a magnetic field are considered. The theoretical results show the constructive contribution of the Rashba effect and the influence of the magnetic field on the thermospin effects. We also show theoretically that material with a high figure of merit can be obtained by tuning the Zeeman splitting energy only.